Joint risk assessment of drought and heat stroke in rainfed maize in Córdoba, Argentina - Antonio de la Casa; Gustavo Ovando; Guillermo Díaz; Pablo Díaz; Fernando Soler; Juan Clemente; Karina Torterolo; Lorenzo Gabba (Next Sustainability)
Drought and heat stress are adverse contingencies for agriculture that, when they occur simultaneously, amplify the productivity losses. This study investigates the risk of the joint occurrence of water scarcity and excessive heat on maize crops in the rainfed agricultural region of Córdoba, Argentina between 1970 and 2021. Meteorological records from 7 stations of the National Meteorological Service (SMN) in the region were used, comprising daily values of precipitation, minimum temperature and maximum temperature (Tx). Drought episodes were expressed using the Standardized Precipitation Evapotranspiration Index (SPEI), which assesses the difference between precipitation (PP) and potential evapotranspiration (EP). Using Tx and considering a threshold of 35°C, heat stroke events were represented by the following indicators on a monthly scale: Mean maximum temperature (Txm), Absolute maximum temperature (Txa), Number of days with Tx≥ 35°C (N°d_Tx≥35), Thermal sum above the threshold (ST>35), and the Standardized Maximum Temperature Index (STxmI), which was obtained similarly to SPEI. The probabilistic and frequency assessment for Tx≥ 35°C reaches a maximum in December and January, with monthly mean values of 25 % in Villa Dolores (VD), 22 % in Villa de María de Río Seco (RS), 13 % in Marcos Juárez (MJ) and Laboulaye (LB), 11 % in Pilar (PO), and 8 % in Río Cuarto (RC). The maximum probability values of Tx≥ 35°C occur immediately before or during the maize flowering stage, a critical phase for both adverse events. There is a generalized inverse relationship between drought and heat stress, which is tighter across the entire region when SPEI and STxml values integrated every three months are used. Although this negative correlation is present throughout the year, it is particularly notable in December and January. Considering more specific indicators to express the heat stroke threat, both N°d_Tx≥ 35 and ST> 35 exhibit a quadratic relationship with SPEI, such that the risk of maize productivity loss associated with water scarcity increases due to the synergistic effect with heat stress. According to the bivariate normal probability function, the joint risk of both factors occurs in approximately 7–10 % of the years in both December and January, corresponding to roughly half of the drought and heat stroke episodes considered independently.